Near real-time management of spectral interferences with portable X-ray fluorescence spectrometers: application to Sc quantification in nickeliferous laterite ores. Issue 3 (2021) - Lacroix, Elodie; Cauzid, Jean; Teitler, Yoram; Cathelineau, Michel
No abstract available